The Maelstrom of Paris Based on a Novel by Germaine Acremant - Coppola, Antonio; Acremant, Germaine (Flicker Alley, 2021)
A well-told story of a woman who thinks she prefers a life of glory on stage in Paris to life with her Scottish lord of a husband in his castle. [mubi.com]
Keywords: Blu-Ray-Disc